Ouvir, contar, reviver e recontar: narrativas de/sobre educadores matemáticos que atuaram no Pacto Nacional Pela Alfabetização Na Idade Certa - Vasconcelos, Lívia de Oliveira (Universidade Federal de São Carlos, 2021)
I participated in the National Pact for Literacy in the Right Age from 2014 to 2017, which allowed me to follow different phases of this public policy: the mathematical literacy cycle in 2014, the discussion on interdisciplinary practices in 2015, the cooling of actions in 2016 and the closure abrupt of the program in 2017. Mobilized by my experience in the program, I chose it as the study theme. This research was carried out with the collaboration of three Mathematics Educators who worked in the genesis of the PNAIC: Carlos Vianna, Emerson Rolkouski – organizers of the PNAIC mathematics training notebooks – and Antonio José Lopes Bigode, who assumed a consultant role in the organizational dynamics of books. These collaborators gave me narrative interviews, through which they introduced themselves to me, telling how they became Mathematics Educators, describing which paths led them to the PNAIC and which projects they were engaged in at the time they were interviewed. The experiences narrated by them, as well as my own experience in carrying out this research, constitute the phenomenon that I investigate narratively, based on the theoretical contributions of Clandinin and Connelly. My general objective is to understand how the experiences of these three Mathematics Educators culminated in the origin of the PNAIC in mathematics in the way in which the program was presented. I do this through four narratives written by me, based on what was narrated by my collaborators. The first one is supported by the interview with Carlos Vianna, who presented me the challenges of putting different authors to work collaboratively and integrated in the PNAIC. Emerson told how the organizers of the mathematics training books were chosen and revealed how his role in other public policy, which preceded the PNAIC, was an important factor in his being invited to assume the position of organizer. Both Emerson and Carlos mentioned a third Mathematical Educator who, being a renowned name in the production of mathematics teaching material, was called upon by them to act as a consultant in the preparation of training materials: Bigode. Bigode, when telling me about the PNAIC, made an inversion of perspective, showing how the program demanded from the academic community a reinvention both in the way of working and in the way of communicating. In the fourth narrative, I resume the legacies of important Mathematics Educators cited by the interviewees as references that formed them, and whose ideals influenced the decisions they took at the PNAIC: Lydia Lamparelli and Romulo Lins. Finally, I present the thesis I built based on the testimony of my collaborators and the interpretive and analytical process I carried out as a researcher.
Listening, telling, relivering and retelling: narratives from/about mathematical educators who worked in the Nacional Pela Alfabetização Na Idade Certa
Keywords: PNAIC; Formação de professores; Educação matemática; Pesquisa narrativa; Teacher education; Mathematical education; Narrative inquiry; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO